3x+2(1-x)=2x+5(1-x)

Simple and best practice solution for 3x+2(1-x)=2x+5(1-x) equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 3x+2(1-x)=2x+5(1-x) equation:


Simplifying
3x + 2(1 + -1x) = 2x + 5(1 + -1x)
3x + (1 * 2 + -1x * 2) = 2x + 5(1 + -1x)
3x + (2 + -2x) = 2x + 5(1 + -1x)

Reorder the terms:
2 + 3x + -2x = 2x + 5(1 + -1x)

Combine like terms: 3x + -2x = 1x
2 + 1x = 2x + 5(1 + -1x)
2 + 1x = 2x + (1 * 5 + -1x * 5)
2 + 1x = 2x + (5 + -5x)

Reorder the terms:
2 + 1x = 5 + 2x + -5x

Combine like terms: 2x + -5x = -3x
2 + 1x = 5 + -3x

Solving
2 + 1x = 5 + -3x

Solving for variable 'x'.

Move all terms containing x to the left, all other terms to the right.

Add '3x' to each side of the equation.
2 + 1x + 3x = 5 + -3x + 3x

Combine like terms: 1x + 3x = 4x
2 + 4x = 5 + -3x + 3x

Combine like terms: -3x + 3x = 0
2 + 4x = 5 + 0
2 + 4x = 5

Add '-2' to each side of the equation.
2 + -2 + 4x = 5 + -2

Combine like terms: 2 + -2 = 0
0 + 4x = 5 + -2
4x = 5 + -2

Combine like terms: 5 + -2 = 3
4x = 3

Divide each side by '4'.
x = 0.75

Simplifying
x = 0.75

See similar equations:

| 91-c=4 | | 5i(i-6)=0 | | 4x+-3(1-x)=3x+5(1-x) | | 2x^3-6x^2-48x+1=8 | | (5+3i)(2-6i)= | | -18+2w+40-5w+8=-9 | | (5y+6)(6y+5)=0 | | 4x+2(x+2)=5(x+1) | | 2x+-3(1-x)=0x+4(1-x) | | (w)=12w^2+17w-40 | | Y+112=334 | | 2(2x+x)+2(10+5)=x+x+20+15(1+1) | | x^3+4x^2-3x=0 | | f(w)=12w^2+17w-40 | | (3d+5)(d-7)=0 | | 7-8s+5s+7+4s= | | (5i+4)(i+4)=0 | | -4x+4(1-x)=3x+0(1-x) | | 0.6w=0 | | 5p=30-10n | | 4x^2-x=17 | | 7j(8j-1)=0 | | 3x-5(1-x)=-2x+3(1-x) | | 1/5*x=210 | | 10.36+23.199x=56.758 | | (6x+7)(4x+3)=0 | | 3x+21=16x-10 | | 7c^4=-1512c | | -6÷(-3/7) | | -5x-66-6x+30=118 | | 5=-16t^2+26t | | -4x+3(1-x)=-5x+-1(1-x) |

Equations solver categories